Object-scalable mesh-based coding of synthetic and natural image objects - Altunbasak, Y. (International Conference on Image Processing, 1997)
This paper presents an object-based image coding scheme, where each image object is encoded individually, provided that their boundaries are specified. This allows object-based quality scalability, in addition to mixing lossy and lossless coding modes depending on the requirements of each image object. Furthermore, we propose a new object coding method using 2-D mesh-based image sampling in which the quadrilateral mesh patches are warped into square blocks, and encoded by traditional data/waveform coding methods. Experimental results on test images are provided.